Pengelolaan Pembiayaan Pendidikan di Sekolah Menengah Pertama Swasta - Siti Fatmawati; Nugraha, Mulyawan Safwandy (Epistemic: Jurnal Ilmiah Pendidikan, 2024)
Effective management of education financing is crucial for ensuring the quality and sustainability of education, particularly in private schools that frequently encounter significant financial challenges. This study aims to examine and analyze the financial management strategies employed at SMP Islam Bakti Asih, a private school in Indonesia, to demonstrate how this institution successfully navigates financial constraints while enhancing educational quality. Utilizing a qualitative research approach with a case study design, data were gathered through in-depth interviews, direct observations, and document analysis. The findings reveal that the school effectively implemented financial strategies, including diversification of funding sources, efficient emergency fund management, and active stakeholder involvement in the budgeting process. These practices have contributed to both financial stability and improved educational outcomes. The study’s implications suggest that adaptive and inclusive financial management approaches can significantly bolster the financial sustainability of educational institutions, providing a valuable model for other schools facing similar financial difficulties to consider adopting.